Les grands lacs à l'épreuve de l'anthropocène - Dorioz, Jean-Marcel (éditions Quae, 2023)
Many of the world's large lakes are, in fact, not large enough to cope with the uses to which they are put by human activities, as they have been going on for over a century. The limits of these continental-scale macro-ecosystems are reflected in a whole series of pathologies that affect them and are accompanied by a deterioration in the ecosystem services provided: fishing, water supply, self-purification, dilution of pollution, cultural and recreational services, etc. In addition, all of the tensions involved are now exercised in a context of multi-stress due to climate change. The "large lake" size, inertia and complexity with which it endows the systems concerned, results in new conditions of exposure and responses, difficult to integrate in terms of management. The book offers a multidisciplinary analysis of various restoration experiments carried out on large lakes around the world (successes and failures). Rich in lessons on the safeguarding and preservation of the world's lake heritage, this study opens up avenues of reflection on the future ecological challenges to be met in order to prepare the "lake-watershed-society" systems for the new situation, in terms of climate and pollution. This book is intended for students, teachers and researchers, lake managers, as well as the general public interested in the preservation and restoration of large lakes.